Intraindividual genome expression analysis reveals a specific molecular signature of psoriasis and eczema - Quaranta, Maria; Knapp, Bettina; Garzorz, Natalie; Mattii, Martina; Pullabhatla, Venu; Pennino, Davide; Andres, Christian; Traidl-Hoffmann, Claudia; Cavani, Andrea; Theis, Fabian J.; Ring, Johannes; Schmidt-Weber, Carsten B.; et al. (Science Translational Medicine, 2014)
Previous attempts to gain insight into the pathogenesis of psoriasis and eczema by comparing their molecular signatures were hampered by the high interindividual variability of those complex diseases. In patients affected by both psoriasis and nonatopic or atopic eczema simultaneously (n = 24), an intraindividual comparison of the molecular signatures of psoriasis and eczema identified genes and signaling pathways regulated in common and exclusive for each disease across all patients. Psoriasis-specific genes were important regulators of glucose and lipid metabolism, epidermal differentiation, as well as immune mediators of T helper 17 (TH17) responses, interleukin-10 (IL-10) family cytokines, and IL-36. Genes in eczema related to epidermal barrier, reduced innate immunity, increased IL-6, and a TH2 signature. Within eczema subtypes, a mutually exclusive regulation of epidermal differentiation genes was observed. Furthermore, only contact eczema was driven by inflammasome activation, apoptosis, and cellular adhesion. On the basis of this comprehensive picture of the pathogenesis of psoriasis and eczema, a disease classifier consisting of NOS2 and CCL27 was created. In an independent cohort of eczema (n = 28) and psoriasis patients (n = 25), respectively, this classifier diagnosed all patients correctly and also identified initially misdiagnosed or clinically undifferentiated patients.
CRIS-Team Scopus Importer:2023-03-08